Effect of economic animosity on consumer ethnocentrism and product-country images. A binational study on the perception of Germany during the Euro crisis. Issue 1 (February 2016) - De Nisco, Alessandro; Mainolfi, Giada; Marino, Vittoria; Napolitano, Maria Rosaria
Abstract: During the recent Euro crisis, Germany's push for austerity has prompted resurgence in anti-German sentiment in some European nations. This study contributes to the literature on consumer animosity, ethnocentrism and country of origin effect by proposing a comprehensive model that analyses: a) the relationship between economic animosity towards a foreign nation and consumer ethnocentrism and b) their mutual effect on the perception of the general image of a country perceived as hostile, the evaluation of the products associated with that country (product beliefs) and the foreign product acceptance (product receptivity). The research model has been tested on a sample of Italian and Spanish graduate students with regard to the image of Germany. Results show that economic animosity does not affect the perceived level of either general country image or product beliefs, but it is negatively associated with product receptivity. This study also supports the relationship between economic animosity and consumer ethnocentrism; thus, consumers that feel anger towards a foreign country will favor domestic products, avoiding foreign ones. Based on results, the paper concludes with a discussion of theoretical and managerial implications and provides suggestions for further research.